A rare presentation of acute hyperglycemia with secondary mania: a case report - Padma, Kumari; Fernandes, Sharol; Hegde, Supriya (International Journal of Research in Medical Sciences, 2019)
This case report aims to highlight the diagnostic challenges in consultation-liaison psychiatry in case of Type 1 Diabetes Mellitus. Author report the case of a 60-year-old male who presented to the Psychiatry OPD with first episode of mania. Although hypoglycaemia is known to be associated with multiple psychiatric manifestations, the incidence of psychiatric symptoms and disorders in association with hyperglycaemia is not well reported. This case report highlights the rare presentation of secondary mania in a patient with Type 1 Diabetes Mellitus.